Preferred parental method of post-operative tonsillectomy and adenoidectomy follow-up (phone call vs. clinic visit). (January 2017) - Anderson, Martin E.; Brancazio, Brianna; Mehta, Deepak K.; Georg, Matthew; Choi, Sukgi S.; Jabbour, Noel
Abstract: Introduction: Tonsillectomy is the second most common procedure performed in the United States. Over 530, 000 tonsillectomies are performed on children under 15 years of age in the United States, accounting for 16% of surgeries in this age group, resulting in missed school for patients of school-age and also resulting in missed work for caregivers. This study compared parent preferences for in-clinic follow-up (CFU) to telephone interview follow-up (TFU) after tonsillectomy. Materials and methods: One hundred twenty-one parents of children who underwent a tonsillectomy and/or adenoidectomy were recruited to complete a survey about their child's post-operative visit. Results: Statistical analyses were performed using t -test, Wilcoxon rank-sum, and Fischer's exact tests where appropriate. 60.3% of the surveys were completed as a TFU and the remainder were completed as a CFU. There were no statistical differences in the children's age, the time to follow-up, satisfaction with their follow-up, or the frequency of unresolved symptoms. Of parents receiving TFU, 91.8% disagreed they would have preferred a CFU, with 86.3% strongly disagreeing, and only 5.5% expressing that they would have preferred a CFU. Of the parents with CFU, 47.9% expressed a preference for a TFU. For CFU, 43.9% of parents missed work and 58.1% of their school-age children missed school. Conclusion: Our study results indicate that parents receiving phone follow-up strongly preferred this method to an in-clinic follow-up, and that nearly half of all parents receiving in-clinic follow-up would have preferred a telephone follow-up. In select patients, telephone follow-up after tonsillectomy may increase patient satisfaction and decrease days of missed work and school.